Wolves and wild ungulates in the Ligurian Alps (Western Italy): prey selection and spatial-temporal interactions - TORRETTA, ELISA; Matteo Serafini; Camille Imbert; Pietro Milanesi; Alberto Meriggi (Mammalia, 2017)
We propose the integration of different noninvasive sampling methods to the study of predator-prey interactions. We analyzed the diet of the wolf (Canis lupus) to point out its elective prey and we investigated its spatial and temporal interactions with prey species from December 2012 to November 2014 in the Ligurian Alps (Southern Alps, Italy). In this area, the wolf is the only large predator, and there is a rich wild ungulate community consisting of four species. Our analyses showed that the most consumed species by wolves were the wild boar (Sus scrofa) and the roe deer (Capreolus capreolus). To successfully hunt these species, wolves need to share their spatial range, searching for them in the most suitable habitat types and in the periods of the diel cycle during which they are mainly active. Fallow deer (Dama dama) and chamois (Rupicapra rupicapra) consumption was low, and wolves showed also relatively low overlap with these species. Our results suggest that wolves might be firstly specialized on wild boar predation, as they showed substantial spatial and temporal overlap with this species, and secondly on roe deer predation, especially during the denning season when they probably take advantage of the presence of fawns.